POLA ASUH SINGLE PARENT DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN ISLAM PADA ANAK USIA 15-17 TAHUN DI DUSUN MELATI DESA SEBUBUS TAHUN 2022-2023 - Purwanti, Yati Purwanti; Susilawati; M. Sabiqul Huda (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The aim of this research is to reveal the values of Islamic education, single parent parenting patterns, and find out what obstacles single parents face in instilling Islamic educational values in children aged 15-17 years in Melati Hamlet, Sebubus Village in 2022. -2023. This research uses a phenomenological approach and qualitative research type. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data display, data verification and drawing conclusions. The data checking and validity techniques used are triangulation and member check. Based on the data analysis carried out, the research results show that the values of Islamic education provided by single parents are the value of moral education towards Allah SWT, morals towards others and morals towards the environment. The single parent parenting style in instilling Islamic educational values is a democratic parenting style, while other parties provide the value of moral education, namely at the school level by working together between parents and teachers at school, peers, and then the surrounding environment to guide children. children to become better individuals in the future. The obstacles experienced by single parents in instilling Islamic educational values are primarily the problem of limited time to educate children's morals, because time is divided into earning a living for the family.